Violence in Human Nature in William Golding’s The Inheritors - Ahmed, Shawnm Marif (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Through the portrayal of Neanderthals and Homo sapiens "new man" and their relation to each other, Golding's novel The Inheritors explores the violent and antagonistic characteristics of human nature throughout history and shows the social elements of behavior of primitive people in the ancient world. This novel has its own literary merit both in form and content. The subject of violence can be found in different conceptualized approaches: violence as inseparable part of human nature, hence entangled with its other facets (other emotions of human like desire for power, feeling of envy or disgust, etc.); violent acts are often defended by sacred mythological and religious rituals and justified by demonizing other human beings. Another concept is to see violence as a mode of survival and as a way to dominate others. Moreover, for the matter of methodologies within literary theory, the paper benefits from many approaches which are commonly used in studying the literary works like moral-philosophical and sociological criticism. This paper is structured into two main sections with various divisions. In section one the relationship between literature and its implications upon human nature and the nature of violence itself is discussed. In section two, the concept of violence in the novel as emotional and behavioral manifestations of human nature is analyzed within the text along with those messages and ideas that are implicated inexplicitly.